Pengaruh Pemberian Beberapa Konsentrasi Bahan Pengawet Floralife terhadap Kesegaran Bunga Potong Hortensia (Hydrangea macrophylla) - NI MADE WINANTHI MILENIADEWI; I NYOMAN GEDE ASTAWA; I MADE SUKEWIJAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Effect of Several Concentrations of Floralife Preservatives to Hyrangea (Hydrangea macrophylla) Cut Flower Freshness Hydrangea (Hydrangea macrophylla) is one type of flower that can be used as cut flowers but has a short vase life of flower freshness. One way that can be done to prolong flower freshness of cut flowers is by using pulsing solution. This research aims to study the use of cut flower preservatives and to obtain the best concentration of pulsing solution using Floralife preservatives in maintaining the freshness of hydrangeas. This research was conducted from January to March 2022 at the Agronomy and Horticulture Laboratory, Faculty of Agriculture, Udayana University. This study used a completely randomized design (RAL) based on single factor of concentration of Floralife preservatives which consisted of distilled water (P0), Floralife concentration of 5,000 ppm (P1), 7,500 ppm (P2), 10,000 ppm (P3) and 12,500 ppm (P4). The results showed that the pulsing solution using Floralife preservative with a concentration of 10,000 ppm (P3) gave the best results, the vase life of hydrangea cut flowers reached 12.8 days (or 8.4 days longer than soaked with distilled water) with the highest total absorbed solution.